Hepatitis B immunisation among invasive cardiologists: poor compliance with United Kingdom guidelines. Issue 6 (December 1995) - Prendergast, B. D.; Andrews, N. P.; Thomas, A.; Davies, L.; McCabe, M.; Penny, W. J.
Abstract : OBJECTIVES--To assess the compliance of invasive cardiologists in the United Kingdom with recently accepted national guidelines on the protection of health care workers and patients from hepatitis B. To determine levels of awareness of the infectivity and prevalence of the virus and current attitudes towards screening of patients before cardiac catheterisation and surgery. DESIGN--Anonymous postal survey by questionnaire from the University Hospital of Wales, Cardiff. The questionnaire established the respondent's position, knowledge of hepatitis B, current immunological state, and policy towards the routine screening of patients for hepatitis B carriage. PARTICIPANTS--All British cardiologists of consultant or senior registrar grade involved in invasive procedures. RESULTS--The response rate was 78% (211/271). 20% of respondents had never been vaccinated against hepatitis B and about a third of those vaccinated had not complied correctly with the recommended immunisation regimen. There was little uniformity in practices for screening patients for hepatitis B carriage before invasive procedures, and the level of knowledge concerning the prevalence of hepatitis B and the risks of inoculation was poor. CONCLUSIONS--Invasive cardiologists are at high risk of inoculation with hepatitis B. Nationally agreed guidelines are designed to protect both medical staff and patients against the risk of infection but currently they are ill heeded.